Food packaging use and post-consumer plastic waste management: a comprehensive review - Luigi Operato; Alberto Panzeri; Gaia Masoero; Andrea Gallo; Leonardo Gomes; Wael Hamd (Frontiers in Food Science and Technology)
In 2021, the packaging sector emerged as the largest source of plastic waste in Europe, accounting for about 40% of the total demand for plastics. On average, an EU citizen produced 35.9 kg of waste from plastic packaging, with a 27% increase over the last 10 years. Despite advances in material efficiency and sustainability efforts, the average recycling rate of plastic packaging in the EU was around 40% in 2022, significantly lower than that of paper and cardboard packaging (83.2%) and metals (76.9%). The Food and Beverage (F&B) sector is an extensive user of packaging, driving the demand for innovative solutions to maintain food quality and safety while minimizing environmental impact. In light of these challenges, this comprehensive review examines the expanding use of packaging within the F&B sector and the management of post-consumer plastic waste at the EU level. It scrutinizes the technical, economic, and regulatory trade-offs in packaging deployment and disposal, emphasizing the need for supply chain collaboration to devise effective solutions. The study provides an overview of EU regulations on health and safety, sustainability, and labeling requirements for F&B packaging materials and products. It also explores the optimization of packaging for food business operators and supply chain management practices as well as current waste management strategies for post-consumer plastic waste, focusing on mechanical and chemical recycling and adherence to regulatory targets. Additionally, it identifies barriers to adopting sustainable packaging alternatives and discusses the impact of packaging design on recyclability and consumer acceptance. The study concludes with future research and industry opportunities, highlighting innovative packaging solutions that balance health and safety, sustainability, and cost-effectiveness.